Isolasi dan identifikasi bakteri asam laktat pada bekasam ikan nila (Orechromis niloticus) dengan penambahan dadih - Noor Ira Sari; Tjipto Leksono; Cindi Harta Yuliana (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Bekasam is a fermented fish product with an additional carbohydrate source that has a salty and sour. The purpose of the research was to determine the effect of adding dadih at different concentrations (without dadih, 5%, 10%, and 15% dadih based on fish meat weight) to carp bekasam on the sensory evaluation, pH value, total lactic acid bacteria and the type of lactic acid bacteria grown on carp bekasam. The research method used is experimental and designed as a completely randomized design (CRD) for sensory evaluation, pH values, and total lactic acid bacteria. Meanwhile, the methods of descriptive were used for identifying the types of lactic acid bacteria. The results showed that sensory evaluation is the value of odor (8.2), taste (7.9), texture (7.9), appearance (8.0), pH value (4.83; 4.58; 4.52; 4.37), and total lactic acid bacteria (1.5 x 106; 2.1 x 106; 3.2 x 106; 5.3 x 106 cfu/ g). Bekasam with the addition of 5% dadih gave the best results but was not significantly different from the results of the addition of 10% dadih. Thus, adding 5% dadih is used more efficiently in the production of bekasam. The morphological and physiological bacteria isolated from carp bekasam without adding dadih were Bacillus sp. Meanwhile, the bacteria isolated from carp bekasam added with dadih (5, 10, and 15%) were Lactobacillus sp.